Exploring juvenile court outcomes as a function of judge‐youth characteristics and interactions. (9th April 2022) - Knoche, Victoria A.; Marsh, Shawn C.; Skinner‐Ling, Tahliah
Abstract: This study examined judge‐juvenile verbal interaction characteristics, demographics, and demographic match at adjudication and their associations with juveniles' behavioral outcomes. Data were collected from audio recordings of hearings and case files from 86 delinquency cases adjudicated in an urban juvenile court in the Southwestern United States as part of a larger research project involving observable procedural justice. Results suggest that some juvenile, judge, and match characteristics had significant associations with both judge‐juvenile interactions (e.g., length of conversations) and juvenile case outcomes (e.g., fewer continuances). We detail these findings and offer considerations for court practice.